Remittances and morality: family obligations, development, and the ethical demands of migration. Issue 11 (18th August 2021) - Simoni, Valerio; Voirol, Jérémie
ABSTRACT: Remittances have moral dimensions that, albeit implicitly addressed in migration literature, have not yet been the focus of explicit attention and analysis by social scientists. Building on recent developments in the anthropology of ethics and morality, this article proposes theoretical and analytical pathways to address this important but often neglected aspect of remittances. It does so mainly via a critical analysis of existing scholarship on remittances, and ethnographic data drawn from research among Cuban migrants in Cuba and Spain. The reflexive scrutiny of scholars' moral assumptions about remittances opens the way for the study of the moral dilemmas and ethical demands articulated by remittance senders and recipients. Family roles and obligations, and the uses of the money sent by migrants, are identified as key areas of moral difficulty. Their analysis shows how remittances inform moral reassessments of family relations, individual responsibility, economic practice, and development. The notion of 'moral remittances' is proposed as a heuristic comparative tool that serves to illuminate the moral aspects of remittances. This notion is put into perspective to complement and reconsider more metaphorical takes on remittances, notably the concept of 'social remittances', of which it helps reveal some epistemological limitations while opening future research avenues.